THE INFLUENCE OF GREEN MARKETING STRATEGY ON PURCHASING DECISION WITH MEDIATION ROLE OF BRAND IMAGE - Asyhari, Asyhari; Yuwalliatin, Sitty (Universitas Brawijaya, Indonesia, 2021)
This study aims to determine and analyze the influence of green marketing, corporate social marketing, and green product innovation on purchasing decisions with the brand image as an intervening variable. The population is consumers who purchase go green products in central java. By using the purposive sampling technique, obtained a total sample of 140 respondents. The analysis tool is the analysis path, which was previously tested for validity, reliability, and the classic assumption test. The test results show that green marketing, corporate social marketing, and green product innovation have a positive influence on brand image. Green marketing, corporate social marketing, green product innovation, and brand image positively influence purchasing decisions. Brand image can be an intervening variable between green marketing and purchasing decisions, while brand image can be an intervening variable between corporate social marketing and purchasing decisions. Brand image can be an intervening variable between green product innovation on repurchase. The more the company can innovate on environmentally-friendly products, the more it will improve the positive image to increase consumers' decisions. Future studies should consider green perceived quality, brand awareness, and brand trust to understand consumer purchasing decisions better.